1980
DOI: 10.1159/000149174
|View full text |Cite
|
Sign up to set email alerts
|

Bunyaviridae

Abstract: The family Bunyaviridae comprises over 200 viruses (serotypes, subtypes, and varieties) that infect vertebrates and/or invertebrates. Four genera of viruses have been defined (Bunyavirus, Nairovirus, Phlebovirus, and Uukuvirus). The main characteristics of the member viruses are: (i) the virus particles are for the most part uniformly spherical, 80–110 nm in diameter, and possess a unit membrane envelope from which protrude polypeptide spikes 5–10 nm long; (ii) the viruses have three helical nucleocapsids, oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
0
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(137 citation statements)
references
References 13 publications
5
131
0
1
Order By: Relevance
“…Thus, the tentative classification of a new isolate could be made by comparison of its virus-specified proteins with known serotypes and confirmed by serology and analysis of the RNA. The protein and migration patterns were similar to those of BUN virus, the prototype of the Bunyavirus genus, and support serological data for the inclusion of the Simbu serogroup in this genus, rather than one of the other four genera (Bishop et al, 1980;Bishop, 1986).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, the tentative classification of a new isolate could be made by comparison of its virus-specified proteins with known serotypes and confirmed by serology and analysis of the RNA. The protein and migration patterns were similar to those of BUN virus, the prototype of the Bunyavirus genus, and support serological data for the inclusion of the Simbu serogroup in this genus, rather than one of the other four genera (Bishop et al, 1980;Bishop, 1986).…”
Section: Discussionsupporting
confidence: 69%
“…The Bunyaviridae family of arthropod-borne viruses comprises four genera (Bunyavirus, Nairovirus, Phlebovirus, Uukuvirus), and possibly a fifth genus (Hantavirus), as well as several unassigned members (Bishop et al, 1980;Bishop, 1986). Viruses have been assigned to individual genera primarily on serological and morphological criteria; more recently these assignments have been substantiated by biochemical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of other possible members of the Bunyaviridae that were also originally isolated in Australia have shown that they are either (a) clearly bunyaviruses, e.g., viruses within the Sinibu serogroup (McPhee and Deila-Porta, 1981), or (b) closely resemble bunyaviruses, e.g., Mapputta, Kowanyama (McPhee, personal communication) and Belmont viruses (McPhee and Westaway, 1981a). Because of the medical and veterinary importance of many tnembers of the Bunya-viridae (Bishop and Shope, 1979), al! new bunyavirus isolates are of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Most arboviruses fulfil the criteria laid down in this definition, but the group is very heterogeneous, containing viruses which, because they have not been fully classified on morphological or physicochemical grounds, are included among the arboviruses for convenience. There are currently 490 known arboviruses and this very large group contains representatives from several different viral families, the most important of which are the families Togaviridae, Flaviviridae, Bunyaviridae, Reoviridae and Rhabdoviridae (Bishop et al, 1980;Rehle, 1989).…”
Section: Pathogens and Diseasesmentioning
confidence: 99%